PENGEMBANGAN MULTIMEDIA PEMBELAJARAN “ACIL (AKU CINTA LINGKUNGAN)” UNTUK MENSTIMULASI KARAKTER PEDULI LINGKUNGAN ANAK USIA 5-6 TAHUN - Hafaz Kiasatina, Aghnesia; Hapidin, Hapidin (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2022)
This development research aims to produce a media that can be used to introduce and stimulate the character of caring for the environment in children, especially at the age of 5-6 years. It is hoped that by using this multimedia, children's awareness and sensitivity about the environment can develop. This research uses an innovative work method with the ADDIE development model. There are two stages of analysis, namely the expert review stage and the trial stage. The subjects of this study were material experts and media experts as validators, five children aged 5-6 years, one kindergarten teacher and two parents. The object of this research is a digital learning multimedia called ACIL (Aku Cinta Lingkungan). Based on the validity test of material experts, ACIL multimedia got a percentage of 97.9% with very feasible criteria. Based on the validity test of media experts, ACIL multimedia gets a percentage of 90.4% with very decent criteria. Based on the results of trials on children, ACIL multimedia got a percentage of 80% with very feasible criteria and based on the results of trials on teachers and parents, ACIL multimedia got a percentage of 90.4% with very feasible criteria. Based on the research results, the learning multimedia